Bentuk Badan Usaha Berbadan Hukum Perseroan Dan Organ-Organ Perseroan: Komparasi Berdasarkan Hukum Di Indonesia Dan Di Singapura - Juniar Tambunan, Katherine (Universitas Sang Bumi Ruwa Jurai, 2024)
Indonesia and Singapore have differences in legal systems. Indonesia applies the Continental European legal system or Civil Law System while Singapore uses the Anglo-Saxon legal system or Common Law System. This difference has implications for the company law in both countries. Thus, this paper is designed to identify the comparison regarding the legal form of business entities and corporate organs between Limited Liability Company Law and its amendments in Omnibus Law on Job Creation which applicable in Indonesia and the Companies Act which applicable in Singapore